2017
DOI: 10.1038/srep44650
|View full text |Cite
|
Sign up to set email alerts
|

Exercise rescues obese mothers’ insulin sensitivity, placental hypoxia and male offspring insulin sensitivity

Abstract: The prevalence of obesity during pregnancy continues to increase at alarming rates. This is concerning as in addition to immediate impacts on maternal wellbeing, obesity during pregnancy has detrimental effects on the long-term health of the offspring through non-genetic mechanisms. A major knowledge gap limiting our capacity to develop intervention strategies is the lack of understanding of the factors in the obese mother that mediate these epigenetic effects on the offspring. We used a mouse model of materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 45 publications
12
115
1
1
Order By: Relevance
“…Increases in circulating inflammatory factors as a result of maternal HFD intake result in placental hypoxia (Fernandez-Twinn et al 2017), which impacts placental vascularization (Hayes et al 2012;Li et al 2013), potentially by altering macrophage activation (Zhao et al 2018). Consistent with these observations, we found increased immunostaining of carbonic anhydrase IX, a placental hypoxia marker, in male (P < 0.0001) and female (P < 0.0001) placentas derived from HFD fed dams (Fig.…”
Section: Maternal Hfd Results In Placental Hypoxia and Altered Placensupporting
confidence: 84%
See 1 more Smart Citation
“…Increases in circulating inflammatory factors as a result of maternal HFD intake result in placental hypoxia (Fernandez-Twinn et al 2017), which impacts placental vascularization (Hayes et al 2012;Li et al 2013), potentially by altering macrophage activation (Zhao et al 2018). Consistent with these observations, we found increased immunostaining of carbonic anhydrase IX, a placental hypoxia marker, in male (P < 0.0001) and female (P < 0.0001) placentas derived from HFD fed dams (Fig.…”
Section: Maternal Hfd Results In Placental Hypoxia and Altered Placensupporting
confidence: 84%
“…Increases in circulating inflammatory factors as a result of maternal HFD intake result in placental hypoxia (Fernandez‐Twinn et al . ), which impacts placental vascularization (Hayes et al . ; Li et al .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, other studies of prenatal lifestyle interventions showed no intervention effects on child anthropometrics or other early life metabolic risk factors (Ronnberg, Hanson & Nilsson, ; Tanvig, Vinter, Jorgensen et al ., ). Animal experiments do show that exercise interventions (Fernandez‐Twinn et al ., ; Moser, McDaniel, Woolard, Phillips, Franklin & Gordon, ; Vega, Reyes‐Castro, Bautista, Larrea, Nathanielsz & Zambrano, ) and dietary interventions (Zambrano, Martinez‐Samayoa, Rodriguez‐Gonzalez & Nathanielsz, ) during pregnancy in obese animals can prevent adverse physical health outcomes (Fernandez‐Twinn et al ., ; Vega et al ., ; Zambrano et al ., ) and learning abilities (Moser et al ., ) in the offspring, without affecting offspring memory performance (Moser et al ., ) and social behavior (Moser et al ., ). To the best of our knowledge other measures of neurobehavioral development has not been assessed in animal experiments yet.…”
Section: Discussionmentioning
confidence: 99%
“…Improving these biological mechanisms in turn are expected to improve child development (Van Lieshout & Krzeczkowski, ). Therefore, improving the lifestyle of obese women before and during pregnancy may be of great importance to reduce the potential negative impact of maternal obesity on child development (Alvarez‐Bueno, Cavero‐Redondo, Sanchez‐Lopez, et al ., ; Fernandez‐Twinn, Gascoin, Musial et al ., ; Van Lieshout & Krzeczkowski, ). Indeed, a recent study showed that a lifestyle intervention during pregnancy in obese women was effective in reducing infant adiposity (Patel, Godfrey, Pasupathy et al ., ), but until now no studies have investigated whether maternal lifestyle interventions have beneficial effects on children's neurobehavioral development.…”
Section: Introductionmentioning
confidence: 99%
“…53 Whether interventions aimed at reducing obesity in women of childbearing age could improve maternal and child's health needs to be investigated further. Some animal experiments provide evidence that exercise or dietary interventions during pregnancy could reverse the detrimental effects of maternal obesity on the offspring, [83][84][85][86][87] with potential sex differences. 85,87 In humans however, only a limited amount of studies examined the consequences of reducing maternal obesity on offspring health.…”
Section: Clinical Relevancementioning
confidence: 99%